PRELIMINARY DESIGN OF UNMANNED AIRLAND (PUNA) - Priyahapsara, Istyawan; Mulyani, Sri (Vortex, 2022)
The development of the number of vehicles exceeding the capacity of highways in urban areas causes frequent traffic jams and increases the risk of accidents. This often happens during year-end holidays and Eid holidays. So it is very necessary to monitor traffic density during the annual holiday period to reduce the number of fatalities due to traffic accidents. Monitoring traffic density using helicopters is expensive because of the high fuel consumption and maintenance. So we need a new alternative, namely using Unmanned Aircraft (PUNA) because it is easy to operate and cheap to maintain. So it is very necessary to design PUNA for traffic density monitoring missions. Aircraft for this purpose are classified as small because the payload, namely the camera, only weighs 2 kg. Study obtained the following results: fuselas/body length 1.94 m, wingspan 1.46 m, airfoil NACA 2412. engine OS MAX-40FX, engine located in the nose, take-off Gross Weight 6.11 kg, material weight 321.09 grams, use an Oblique Camera type camera, the camera weight is 2 kg, and the camera position is 3 ft from the nose.